2012
DOI: 10.1016/j.neuropharm.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Stress modulation of drug self-administration: Implications for addiction comorbidity with post-traumatic stress disorder

Abstract: Drug abuse and dependence present significant health burdens for our society, affecting roughly 10% of the population. Stress likely contributes to the development and persistence of drug use; for example, rates of substance dependence are elevated among individuals diagnosed with post-traumatic stress disorder (PTSD). Thus, understanding the interaction between stress and drug use, and associated neuroadaptations, is key for developing therapies to combat substance use disorders. For this purpose, many rodent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 191 publications
(228 reference statements)
1
63
0
1
Order By: Relevance
“…The effectiveness of medications for substance use disorders differs across individuals and even within individuals at different times of their disease process (Heilig et al, 2010b;Koob and Zorrilla, 2010;Heilig et al, 2011;Logrip et al, 2011;Logrip et al, 2012). Based on the reviewed evidence, CRF 1 receptor antagonists would be expected to be most effective if substance use has transitioned to use driven by negative reinforcement ( withdrawal/negative affect ) and to protect against stress-induced relapse ( stress-related craving ).…”
Section: Functional and Genetic Heterogeneity Of Substance Use Disordersmentioning
confidence: 99%
“…The effectiveness of medications for substance use disorders differs across individuals and even within individuals at different times of their disease process (Heilig et al, 2010b;Koob and Zorrilla, 2010;Heilig et al, 2011;Logrip et al, 2011;Logrip et al, 2012). Based on the reviewed evidence, CRF 1 receptor antagonists would be expected to be most effective if substance use has transitioned to use driven by negative reinforcement ( withdrawal/negative affect ) and to protect against stress-induced relapse ( stress-related craving ).…”
Section: Functional and Genetic Heterogeneity Of Substance Use Disordersmentioning
confidence: 99%
“…Interestingly, excessive alcohol drinking and alcohol dependence-related behaviors are blocked by systemic administration of either CRF1 receptor antagonists (Gehlert et al , 2007; Richardson et al , 2008, Gilpin et al , 2008; Edwards et al , 2012) or glucocorticoid receptor antagonists (Dina et al , 2008; Vendruscolo et al , 2012). The CRF/ERK signaling cascade in the CeA has also been implicated in stress and pain sensitization (Ji et al , 2007; Fu et al , 2008; Fu and Neugebauer, 2008; Egli et al , 2012), and these neuroadaptations may facilitate the transition to PTSD with or without co-morbid drug dependence (Egli et al , 2012; Logrip et al , 2012; Moeller-Bertram et al , 2012). Chronic stress is also associated with excessive norepinephrine release in the PFC (Arnsten, 2009).…”
Section: Recent Neurobiological Insights Gained From Animal Models Ofmentioning
confidence: 99%
“…AD and PTSD interact and produce worse outcomes than either disorder alone (Berenz and Coffey, 2012), further complicating treatment. Treating these disorders separately does not address possible common mechanisms and pathways (Logrip et al, 2012; Norman et al, 2012), leading to poorer prognosis (Berenz and Coffey, 2012). Further, McCarthy and Petrakis (2010) found that interventions targeting the symptoms of comorbid PTSD and AD were most effective.…”
Section: Introductionmentioning
confidence: 99%